Brain Network to Placebo and Nocebo Responses in Acute Experimental Lower Back Pain: A Multivariate Granger Causality Analysis of fMRI Data - Shi, Yu; Cui, Shaoye; Zeng, Yanyan; Huang, Shimin; Cai, Guiyuan; Yang, Jianming; Wu, Wen (Frontiers in Behavioral Neuroscience, 2021)
Background and Objective Placebo and nocebo responses are widely observed. Herein, we investigated the nocebo hyperalgesia and placebo analgesia responses in brain network in acute lower back pain (ALBP) model using multivariate Granger causality analysis (GCA). This approach analyzes functional magnetic resonance imaging (fMRI) data for lagged-temporal correlation between different brain areas. Method After completing the ALBP model, 20 healthy subjects were given two interventions, once during a placebo intervention and once during a nocebo intervention, pseudo-randomly ordered. fMRI scans were performed synchronously during each intervention, and visual analogue scale (VAS) scores were collected at the end of each intervention. The fMRI data were then analyzed using multivariate GCA. Results Our results found statistically significant differences in VAS scores from baseline (pain status) for both placebo and nocebo interventions, as well as between placebo and nocebo interventions. In placebo network, we found a negative lagged-temporal correlation between multiple brain areas, including dorsolateral prefrontal cortex (DLPFC), secondary somatosensory cortex area, anterior cingulate cortex (ACC), and insular cortex (IC); and a positive lagged-temporal correlation between multiple brain areas, including IC, thalamus, ACC, as well as supplementary motor area (SMA). In nocebo network, we also found a positive lagged-temporal correlation between multiple brain areas, including primary somatosensory cortex area, caudate, DLPFC and SMA. Conclusion The results of this study suggest that both pain related network and reward system are involved in placebo and nocebo responses. The placebo response mainly works by activating reward system and inhibiting pain-related network, while the nocebo response is the opposite. Placebo network also involves the activation of opioid mediated analgesia system and emotion pathway, while nocebo network involves the deactivation of emotional control. At the same time, through the construction of GC network, we verified our hypothesis that nocebo and placebo networks share part of same brain regions, but the two networks also have their own unique structural features.